Efektivitas Model Blended Learning Terhadap Motivasi Belajar Mahasiswa Pada Mata Kuliah Evaluasi Pembelajaran - Hilda Ashari (Pandega: Jurnal Kajian Pendidikan dan Kepramukaan, 2023)
This research aims (1) to determine the differences in motivation and understanding level of the students between learning model of blended learning and the conventional, and (2) the improvement of students learning motivation and understanding due to the use of blended learning model. This research was a quasi-experimental. The population is the sixth semester students of the academic year 2022/2023 Study Program Informatics and Computer Engineering Education Universitas Negeri Makassar (UNM) as many as 135 students. The selection of the sample of students was done using purposive sampling technique as many as 90 students. Collecting data using test multiple-choice and questionnaire, the data analysis techniques used were statistical parametric t-test with a significance level of 0.05. The results of the research show that (1) there is a difference in learning motivation of the students between learning model of blended learning and conventional learning of 5.690 and there is difference in the understanding level of the students of 8,950 and (2) there is an improvement in learning motivation of the students due to blended learning application with an average of 12.560 and there is an improvement in the understanding level of the student with an average of 31.670.